BTS celebrity endorser and consumer purchase intentions: the mediating impact of attitudes toward ads in Padang City: * - Tesa Febrina; Vidyarini Dwita (Universitas Negeri Padang, 2023)
This research was conducted with the aim of analyzing and knowing the influence of BTS as a celebrity endorser on consumer buying interest in Tokopedia by mediating attitudes towards advertisements in the city of Padang. This type of research is done is quantitative research. The population of this study is the people of Padang who know BTS and have seen BTS advertisements on Tokopedia with a sample size of 225 people or respondents. In this study, an analysis was carried out using SEM PLS with SmartPLS 4.0 Software. the results of this research show that (1) Celebrity endorsers have a positive and significant effect on Purchase Intentions, (2) Celebrity Endorsers have a positive and significant effect on attitudes towards advertising, (3) attitudes towards advertising have a positive and significant effect on consumer purchase intentions ,(4)celebrity Endorser has a positive and significant effect on purchase intention with attitudes toward advertising as a mediating variable.